PERJANJIAN PENGADAAN TANAH KAS DESA SEBAGAI LAHAN KAWASAN INDUSTRI DI DAERAH ISTIMEWA YOGYAKARTA - Anggriani, Reni (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
Special Region of Yogyakarta wants to increase the investment, there are some method that is quite effective in investor, one of them is by developing industrial area. Government Regulation Number 24 of 2009 concerning on Industrial Area explained that industrial area is where the central of Industrial activity that equipped with facilities and infrastructures supported and managed by industrial estate Company which already have Industrial Business License. With that fact, the researcher interest to research on industrial area. Most of the land in Yogyakarta is Sultan Ground and land of village cash, so to organize the investment program, a model of agreement is needed that can guarantee the parties in developing the investment, especially in the Special Region of Yogyakarta. The Methods of this research is literature Legal approach that examines legal materials and other legal materials, with the aim of the existence of guidelines or regulations concerning the procurement of land for industrial area which is Sultan Ground or land of village cash.